Asuhan Keperawatan Pada Tn. R Dengan Post Operasi Soft Tissue Tumor (STT) Gluteal Sinistra Di Ruang Mawar 2 RSUD dr. Soeselo Kabupaten Tegal - Ayu Pujiati; Ahmad Zakiudin (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Soft Tissue Tumor (STT) is an abnormal lump or swelling caused by new cell growth originating from connective tissue. Post-operative STT presents major nursing problems including acute pain, knowledge deficit, and risk of infection that require comprehensive nursing care. This scientific paper aims to describe nursing care for Mr. R with post-operative Soft Tissue Tumor (STT) Gluteal Sinistra in Mawar 2 Ward of RSUD dr. Soeselo Tegal Regency. The writing method used is descriptive with a case study plan through interviews, physical examination, observation, and documentation. Assessment was conducted on February 8, 2026 on Mr. R, a 37-year-old male, who underwent left gluteal tumor removal surgery on February 7, 2026. Assessment results identified three nursing diagnoses: acute pain related to physical injury agent (D.0077), knowledge deficit related to lack of information exposure (D.0111), and risk of infection evidenced by invasive procedure effects (D.0142). After nursing interventions for 2x24 hours on February 8–9, 2026, evaluation showed all three nursing diagnoses resolved: pain scale decreased from 6 to 2, the client was able to re-explain the tumor disease, and the surgical wound was clean without signs of infection. The conclusion of this nursing care shows that the application of deep breathing relaxation techniques, health education, and proper wound care are effective in addressing nursing problems in post-operative Soft Tissue Tumor patients.